Evaluation of Antioxidant Activity and Drug Delivery Potential of Cell-Derived Extracellular Vesicles from Citrus reticulata Blanco cv. 'Dahongpao' - Shunjie Li; Zimao Ye; Lintao Zhao; Yijun Yao; Zhiqin Zhou (MDPI AG, 2023)
Plant extracellular vesicles (PEVs) have attracted increasing attention due to their rich composition, good antioxidant and anti-inflammatory activity, and ability to transport drugs. As a common fruit, citrus is an ideal material for extracting PEVs because of the diversity and abundance of bioactive substances in it. In our study, citrus-derived extracellular vesicles (CEVs) were extracted from red mandarin (Citrus reticulata Blanco cv. 'Dahongpao') and it was found that they contain high levels of lipids, proteins, and carbohydrates. The high levels of total phenols and total flavonoids suggest that CEVs have good chemical antioxidant properties. We also demonstrated through cell experiments that CEVs have significant antioxidant and anti-inflammatory effects. Furthermore, we found that CEVs have an encapsulation rate of 71.5 ± 0.19% and a high drug-carrying capacity of 4.96 ± 0.22% and can enhance antioxidant and anti-inflammatory activity when loaded with tangeretin. Our results show that CEVs contain abundant bioactive components, have low toxicity, exhibit good antioxidant and anti-inflammatory properties, and can serve as drug delivery agents. This study has important implications for utilizing citrus materials and developing natural anti-oxidative and anti-inflammatory biomaterials.